1987
DOI: 10.1002/hep.1840070209
|View full text |Cite
|
Sign up to set email alerts
|

Different susceptibilities to the formation of cholesterol gallstones in mice

Abstract: In the search for an animal model of genetic determinants of cholesterol cholelithiasis, we found strain, gender and individual differences in mice. Male black (C57BL6J) mice had a 50% incidence of cholesterol gallstones after they consumed lithogenic food similar to that used by Tepperman et al. for 2 weeks, whereas similarly treated male agouti (CBA/J) mice and females of both strains were free of gallstones. The male and female mice of both strains were fertile at 8 weeks of age, and the male black mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Later, Fujihira et al [61] found that prevalence of cholesterol gallstones varied from 0% to 100% among six strains of mice. Alexander and Portman [62] observed that, upon being fed the lithogenic diet, C57BL/6 mice were susceptible to gallstone formation, whereas CBA mice were resistant. Recently, Khanuja et al [63••] studied nine inbred strains of mice on the lithogenic diet for 12 weeks and found that differences in gallstone susceptibility between C57L/J and AKR/J strains were determined by at least two Lith genes with Lith1 (for lithogenic gene 1) mapping to mouse chromosome 2 by QTL analysis.…”
Section: Quantitative Trait Locus Study and Lith (Gallstone) Genes Inmentioning
confidence: 98%
“…Later, Fujihira et al [61] found that prevalence of cholesterol gallstones varied from 0% to 100% among six strains of mice. Alexander and Portman [62] observed that, upon being fed the lithogenic diet, C57BL/6 mice were susceptible to gallstone formation, whereas CBA mice were resistant. Recently, Khanuja et al [63••] studied nine inbred strains of mice on the lithogenic diet for 12 weeks and found that differences in gallstone susceptibility between C57L/J and AKR/J strains were determined by at least two Lith genes with Lith1 (for lithogenic gene 1) mapping to mouse chromosome 2 by QTL analysis.…”
Section: Quantitative Trait Locus Study and Lith (Gallstone) Genes Inmentioning
confidence: 98%
“…This diet is known to cause gallstone formation and accumulation of fat in mouse liver (Alexander and Portman, 1987;Nishina et al, 1990). We focused on comparing K8-null with heterozygous and WT mice given that K8-null mice had the most significant keratin alterations in the gallbladder (Figs 2, 3) and liver (Baribault et al, 1994;Caulin et al, 2000;Gilbert et al, 2001;Loranger et al, 1997;Toivola et al, 1998;Toivola et al, 2001;Zatloukal et al, 2000).…”
Section: Effect Of a Lithogenic Diet On Gallbladder And Liver Injury mentioning
confidence: 99%
“…We focused on comparing K8-null with heterozygous and WT mice given that K8-null mice had the most significant keratin alterations in the gallbladder (Figs 2, 3) and liver (Baribault et al, 1994;Caulin et al, 2000;Gilbert et al, 2001;Loranger et al, 1997;Toivola et al, 1998;Toivola et al, 2001;Zatloukal et al, 2000). We used a feeding period of 5 weeks based on the known frequency of mouse gallstone formation (~50-60%) among different mouse strains (though there are significant strain and sex related differences) (Alexander and Portman, 1987;Nishina et al, 1990). As shown in Table 2, the incidence of gallstone formation is similar among the three K8 mouse genotypes, and hence is independent of gallbladder keratin expression level or filament organization.…”
Section: Effect Of a Lithogenic Diet On Gallbladder And Liver Injury mentioning
confidence: 99%
“…Among studies of gallstone formation in animals, Alexander and Portman (4) demonstrated that C57BL/6 mice are susceptible to cholelithiasis, but CBA mice are resistant. In both strains bile was supersaturated with cholesterol but not to the same degree (4). Fujihara et al (5) reported that the prevalence of gallstones varied from 0% to 100% among six strains of laboratory mice.…”
mentioning
confidence: 99%